2015
DOI: 10.1080/09523987.2015.1005426
|View full text |Cite
|
Sign up to set email alerts
|

Scholars and social media: tweeting in the conference backchannel for professional learning

Abstract: Social media are fundamentally changing core practices in various industries. Although surveys indicate that social media are impacting social scientists, we know little about how education scholars, specifically, use social media for their work or professional learning. This article explores how educational scholars incorporated the social media, Twitter, as a conference backchannel. Using qualitative interview data collected from members of the American Educational Research Association (AERA) and considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 26 publications
1
67
1
2
Order By: Relevance
“…Likewise, micro-blogging platforms (e.g., Twitter) are used to stimulate student engagement in the classroom. In particular, Twitter enables students to share their thoughts about a discussion topic within 140 characters [13,31,32,47].…”
mentioning
confidence: 99%
“…Likewise, micro-blogging platforms (e.g., Twitter) are used to stimulate student engagement in the classroom. In particular, Twitter enables students to share their thoughts about a discussion topic within 140 characters [13,31,32,47].…”
mentioning
confidence: 99%
“…Although the way teachers learn has been a constant concern of educational research (Caldwell, Heaton, 2016), the influence and attractiveness exerts on teachers professional learning communities is less investigated. There were studied the reasons for which teachers are part of virtual communities (Trust, 2012), factors that influence the use of Information and Communication Technology (Mumtaz, 2000), the use of social media in teachers' training (Munoz, Pellegrini -Lafont, Cramer, 2014), the communication in social media environments (Li, Greenhow, 2015). All the reviewed research shows an insufficient explored field, an invitation for more investigation.…”
Section: Social Media and Teacher's Learning Communitymentioning
confidence: 99%
“…Given the unique attributes of microblogging tools and mounting popularity of these tools among digital natives, researchers believe microblogging holds great potential to be integrated across varying educational contexts to support both individual and collaborative learning Krutka, Nowell, & Whitlock, 2017;Luo, Dani, & Cheng, 2016;Ricoy & Feliz, 2016;Rohr, Costello, & Hawkins, 2015;Shah, Shabgahi, & Cox, 2016). In face-to-face classroom settings, backchanneling, which means to maintain a real-time communication channel on the side of the primary instructional activity, is a common form of microblogging's educational use in order to enhance audiences' participation and engagement in a live event (Kim et al, 2015;Kimmons & Veletsianos, 2016;Kimmons, Veletsianos, & Woodward, 2017;J. Li & Greenhow, 2015;Tomlinson et al, 2017).…”
Section: Microblogging Use In Educationmentioning
confidence: 99%
“…Microblogging is a type of lightweight online application that allows a burst of multimedia content to be published and shared with others worldwide on the web (Java, Song, Finin, & Tseng, 2007). Research has reported its benefits and potential in allowing instant feedback and comments alongside the main channel of instruction or information (Kimmons & Veletsianos, 2016;Li & Greenhow, 2015;Luo, 2015Luo, , 2016, promoting interaction and engagement (Domizi, 2013;Luo, Smith, & Cheng, 2016;Munoz, Pellegrini-Lafont, & Cramer, 2014), and boosting academic achievement (Junco, Elavsky, & Heiberger, 2013;Kassens-Noor, 2012;Van Vooren & Bess, 2013). Nevertheless, studies that specifically address the process of knowledge construction in the context of microblogging tools have been limited.…”
Section: Introductionmentioning
confidence: 99%